Integrated sustainability assessment of water systems: lessons from the Ebro River Basin. (12th May 2008) - Tabara, J. David; Roca, Elisabet; Madrid, Cristina; Valkering, Pieter; Wallman, Patrik; Weaver, Paul
This paper describes the co-development and implementation of visioning and experimenting exercises, agent-based modelling, and gaming tools in Integrated Sustainability Assessments (ISAs) involving stakeholders. These new tools are aimed at supporting reflexive learning and at building alternative policy relevant knowledge and evaluative paradigms for managing sustainability. The specific case study relates to water management within the Ebro River Basin. Conclusions concern the use of these tools to represent complexity, to learn how conflict and collaboration between agents can be addressed, and to explore the roles played by power regimes, institutional rules, and culture in constraining or enhancing transition in the water domain.